2018
DOI: 10.1002/app.46413
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanically stable dielectric composites based on poly(ether ketone) and BaTiO3 with improved electromagnetic shielding properties in X‐band

Abstract: High‐performance barium titanate (BaTiO3) filled poly(ether ketone) (PEK) composites were prepared by melt compounding with an aim to investigate the effect of BaTiO3 on thermal, thermomechanical, dielectric, and electromagnetic interference shielding behavior of PEK. The content of BaTiO3 in the PEK matrix was varied from 0 to 18 vol %. Scanning electron microscopy studies shows that BaTiO3 particles were uniformly distributed in the PEK matrix up to 13 vol % loading followed by the formation of agglomerates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…BaTiO 3 (0-18 vol%)/poly(ether ketone) (PEK) composites prepared by melt compounding were also investigated for their electromagnetic interference shielding behaviors. 428 The EMI SE increased with ller loading due to the increasing dielectric constant and attained À11 dB ($92% attenuation) at 18 vol% BaTiO 3 loading. PVDF/NiO/BaTiO 3 nanocomposite lms were prepared by the solvent casting method and the overall shielding effectiveness was found to be À11.5 dB.…”
Section: Thicknessmentioning
confidence: 95%
See 1 more Smart Citation
“…BaTiO 3 (0-18 vol%)/poly(ether ketone) (PEK) composites prepared by melt compounding were also investigated for their electromagnetic interference shielding behaviors. 428 The EMI SE increased with ller loading due to the increasing dielectric constant and attained À11 dB ($92% attenuation) at 18 vol% BaTiO 3 loading. PVDF/NiO/BaTiO 3 nanocomposite lms were prepared by the solvent casting method and the overall shielding effectiveness was found to be À11.5 dB.…”
Section: Thicknessmentioning
confidence: 95%
“…Dielectric materials and their composites have also been used in blocking incoming EM waves. 406–437 Lu et al 406 studied the thickness dependence variation of reflection loss against ε ′ and ε ′′ (Fig. 18(a)) and microwave absorption properties of the composites loaded with 10 wt% ZnO@MWCNTs vs. the frequency and thickness at different temperatures (Fig.…”
Section: Dielectric Materialsmentioning
confidence: 99%
“…Titanites are also very promising materials for the construction of EMI shielding polymer composites, mainly due to their high values of dielectric constant (permittivity). Chauchan et al 160 investigated high-performance barium titanate (BaTiO 3 ) filled poly(ether ketone) (PEK) composites for their thermal, thermomechanical and dielectric properties, as well as EMI shielding ability. The results showed that the dielectric constant of the composites increased roughly three times by the incorporation of 18 vol% BaTiO 3 in the frequency range of 8.2–12.4 GHz.…”
Section: Materials Used For Emi Shieldingmentioning
confidence: 99%
“…In our study, the presence of mini-capacitors with high dielectric permitivitty (i.e. the SrTiO3) [44] in the composites and the atomic polarization effect [24] give rise to the improved permittivity at the high frequency band. The increase to high filler loadings, results in an increase in ', which can be related to the finer dispersion of SrTiO3 particles in the composite microstructures [44].…”
Section: Thermal Propertiesmentioning
confidence: 99%